SOSIALISASI “LAWAN PERUNDUNGAN” SEBAGAI UPAYA EDUKASI DAN PERLINDUNGAN ANAK DI SDN 168 DESA MAMPUN BARU, MERANGIN - Widia Putri Febriani; Ditya Putri Wulansari; Habibi; Rizki Apriadi Bahri; Lasmini (AbdiMasya | Hira Institute, 2025)
Bullying remains a serious problem in elementary schools and negatively impacts children's emotional, social, and academic development. This Community Service activity aims to increase students' understanding and awareness of bullying through the "Fight Bullying" socialization program at SD Negeri 168, Mampun Baru Village, Pamenang Barat District, Merangin Regency. The method used is educational and participatory through the delivery of interactive materials, discussions, questions and answers, educational games, and case simulations. Evaluation is carried out through direct observation, reflection, and feedback from teachers. The results of the activity show an increase in students' understanding of the meaning, forms, and impacts of bullying, as well as the growth of empathy, courage to reject, and report bullying. This program effectively supports the creation of a safe, comfortable, and child-friendly school environment and strengthens the role of schools in preventing bullying from an early age.